Evaluation of the Nucleopolyhedrovirus of Anticarsia gemmatalis as a Vector for Gene Therapy in Mammals - Parsza, Cintia N.; Gómez, Diego L.M.; Simonin, Jorge A.; Belaich, Mariano Nicolás; Ghiringhelli, Pablo D. (Current Gene Therapy, 2021)
Background: Baculoviruses are insect pathogens with important biotechnological applications that transcend their use as biological controllers of agricultural pests. One species, Autographa californica multiple nucleopolhyedrovirus (AcMNPV), has been extensively exploited as a molecular platform to produce recombinant proteins and as a delivery vector for genes in mammals because it can transduce a wide range of mammalian cells and tissues without replicating or producing progeny. Method: To investigate if the budded virions of Anticarsia gemmatalis multiple nucleopolhyedrovirus (AgMNPV) species has the same ability, the viral genome was modified by homologous recombination into susceptible insect cells to integrate reporter genes and then it was evaluated on mammalian cell lines in a comparative form with respect to equivalent viruses derived from AcMNPV. Besides, the replicative capacity of AgMNPV´s virions in mammals was determined. Results: The experiments carried out showed that the recombinant variant of AgMNPV transduces and support the expression of delivered genes but not replicates in mammalian cells. Conclusion: Consequently, this insect pathogen is proposed as an alternative to non-infectious viruses in humans to explore new approaches in gene therapy and other applications based on the use of mammalian cells.
Keywords: gene therapy